RE-ORIENTATION OF LEGAL POLICY FOR USING OF FOREIGN WORKERS IN INDONESIAN JUSTICE - Andri Winjaya Laksana; Jarot Jati Bagus (Jurnal Akta, 2021)
The existence of foreign workers, which so far has not been balanced with clear legal arrangements, has in its development led to problems of legal certainty in the field of employment. This writing uses doctrinal research or normative juridical research as for the research results obtained that the re-orientation of the implementation of legal policies on the use of foreign workers has not been able to achieve justice. This is because the legal politics of the use of foreign workers has resulted in reduced job opportunities for domestic workers, which in turn resulted in unemployment and poverty problems. Weaknesses in the implementation of the politics of using foreign workers are the shortcomings in the form of time limits and the amount of use of foreign workers is not clearly regulated in the politics of foreign labor law in Indonesia, then the weakness in the case of dualism in work permits for foreigners in Act No. 13 of 2003 and Act No. 6 of 2011.